THE PLACE OF THE NONVIOLENCE IN THE DEVELOPMENT OF THE HUMANISTIC IDEAS OF THE PHILISOPHY OF EDUCATION - Omelchenko, Y. (Continuing Professional Education: Theory and Practice, 2019)
EDUCATION Based on the principles of the ethics of non violence it is analyzed the activities of the foreign and domestic representatives of this philosophical and ethical political approach that has played a significant role in the development of the modern humanistic education. The philosophical postulates of the ethics of non violence have not lost their urgency; the educational processes undergo cardinal transformations toward humanizing of education. The Soviet activists of the ethics of nonviolence and human rights could only dream about such transformations. But in Ukraine and in some other post totalitarian countries there are some problems with the consolidation of the society around the humanistic principles. They are caused by the inertness of the system, its corruptionality, negative moral and ethical remnants in the relationships at the interpersonal level and the lack of the generally accepted moral authorities.